Clinical and epidemiological characteristics of the 2025 dengue outbreak in Bangladesh - Tamanna Tabassum; Sadia Zaman; Md Mohiuddin Khan; Mohammad Jahid Hasan; Md. Shahabul Huda Chowdhury; Muna Islam; Sadia Islam; Jannatul Fardous; Mehraj Islam; Md. Atiquel Islam Chowdhury; Madhabi Karmaker; Mohiuddin Sharif; et al. (PLOS Neglected Tropical Diseases, 2026)
Background This study aimed to describe the clinical and epidemiological characteristics of patients with dengue fever during the 2025 outbreak in Bangladesh. Methods This multicenter observational study was conducted in four tertiary care hospitals in Bangladesh between June and October 2025. Hospitalized adult patients with laboratory-confirmed dengue infection, defined by a positive NS1 antigen or dengue IgM test, were consecutively enrolled. Demographic characteristics, clinical manifestations, and laboratory parameters were collected through face-to-face interviews using a pretested semi-structured case record form. Physical examination findings and other relevant clinical information were extracted from medical records at the time of hospital admission. Dengue severity was classified according to the revised World Health Organization (WHO) 2009 dengue guidelines. Results A total of 590 adult dengue patients were included in the study with the mean age 34.3 ± 12.6 (SD) years, with clear male predominance (73.7%). Common symptoms included fever (92.7%), headache (82.7%), myalgia (76.9%), arthralgia (68.0%), nausea (59.8%), anorexia (44.7%), vomiting (42.5%), and diarrhea (18.3%). Warning signs were present in 31.5% of patients, most frequently abdominal pain (41.2%), lethargy (18.1%), restlessness (17.3%), fluid accumulation (ascites 16.9%, pleural effusion 9.0%), and respiratory distress (14.6%). Severe dengue was identified in 32.7% of cases, characterized by plasma leakage (16.4%), bleeding manifestations (melena 8.5%, hemoptysis 5.3%), neurological symptoms (confusion 5.3%, convulsions 1.2%), and shock (6.8%). Two deaths were recorded. Conclusion This study found a predominance of young adult males, with nearly one-third developing severe dengue during the 2025 outbreak in Bangladesh.